Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789 (Hymenoptera: Apidae: Centridini) - Vivallo, Felipe (Zootaxa, 2016)
Centris dimidiata (Olivier) is currently considered an easily recognizable species widely distributed throughout the Amazon basin, mainly in Brazil. For much of its taxonomic history, C. atriventris Mocsáry and C. furcata (Fabricius) have been considered its junior subjective synonymies. Such interpretation was apparently due to the lack of a detailed study of the type specimens, misinterpretation of the original descriptions, and inability to study the apparently lost type specimen of C. dimidiata. In this paper, a neotype for C. dimidiata is designated, the species is placed in Centris (Ptilotopus), and C. denudans rubida Gribodo is proposed as its new junior synonymy. Simultaneously, as a result of a detailed study of the type material of C. atriventris and C. furcata, both species are revalidated and their placement in Centris (Melacentris) is confirmed. For all species, the female is redescribed and the male is described for the first time. A lectotype for C. atriventris is designated and new distribution records and a distribution map are provided.